Fluid Metals : the Liquid-Vapor Transition of Metals. - Hensel, Friedrich; Warren, William W., Jr. (Princeton : Princeton University Press, 2014)
This is a long-needed general introduction to the physics and chemistry of the liquid-vapor phase transition of metals. Physicists and physical chemists have made great strides understanding the basic principles involved, and engineers have discovered a wide variety of new uses for fluid metals. Yet there has been no book that brings together the latest ideas and findings in the field or that bridges the conceptual gap between the condensed-matter physics relevant to a dense metallic liquid and the molecular chemistry relevant to a dilute atomic vapor. Friedrich Hensel and William Warren se.
Chapter 6 -- Critical Fluctuations and Interfacial Phenomena 6.1 Fluctuations and the State-Dependent Interaction; 6.2 The Critical Region of Single-Component Fluids; 6.3 Critical Phenomena in Dilute Binary Mixtures; 6.4 Wetting; 6.5 Homogeneous Nucleation of Supersaturated Metal Vapor; Chapter 7 -- High-Temperature/High-Pressure Techniques; 7.1 The lnternally Heated Autoclave; 7.2 Equation-of-State and Electrical Measurements; 7.3 Magnetic Measurements; 7.4 Neutron Diffraction Studies; 7.5 Optical Measurements; 7.6 X-Ray Measurements; Appendix; Index.
Print version record.
IEEE
Keywords: Liquid metals; 9; SCIENCE -- Physics -- General; SCIENCE -- Energy; SCIENCE -- Mechanics -- General; Liquid metals; Electronic books; Electronic books